2017
DOI: 10.1177/1550059417734106
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Dysexcitability May Be a Biomarker of Migraine: A Visual Evoked Potential Study

Abstract: We report neuronal sensitization and impaired habituation in migraine using pattern reversal visual evoked potential (PRVEP) and correlate these with clinical characteristics of migraine. Sixty-five migraineurs and 30 healthy controls were included. A detailed clinical examination was done and migraine characteristics, including migraine trigger, photophobia, phonophobia, and allodynia were noted. Consecutive 5 blocks of PRVEP were recorded averaging 100 epochs at 3 Hz stimuli. The amplitude of N75 and P100 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Another study using VEP has reported decreased habituation during the preictal phase, which became normal during headache with a trend toward elevation during the postictal phase (Judit et al., 2000). Other studies, however, have found no difference across migraine phases, rather there was sensitization along with impaired habituation during headache (Kalita et al., 2018).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Another study using VEP has reported decreased habituation during the preictal phase, which became normal during headache with a trend toward elevation during the postictal phase (Judit et al., 2000). Other studies, however, have found no difference across migraine phases, rather there was sensitization along with impaired habituation during headache (Kalita et al., 2018).…”
Section: Discussionmentioning
confidence: 89%
“…Another study using VEP has reported decreased habituation during the preictal phase, which became normal during headache with a trend toward elevation during the postictal phase (Judit et al, 2000). Other studies, however, have found no difference across migraine phases, rather there was sensitization along with impaired habituation during headache (Kalita et al, 2018). F I G U R E 4 Regression curve and box overlaid with scattered plot diagrams show the correlation of brainstem auditory evoked potential at 60dBSL with clinical parameters and hearing threshold.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Migraine is a multifactorial disease having genetic predisposition and environmental influences. Various studies have reported the basis of neurovascular theory, impaired habituation, and sensitization of cortical, thalamic, and brainstem neurons (7)(8)(9)(10)(11)(12)(13)(14)(15). Chronic migraine (CM) is more disabling compared to episodic migraine (EM) in terms of household productivities, missing family activities, work loss, and direct cost of treatment.…”
mentioning
confidence: 99%